Nggusu Waru-based Social Studies Electronic Book Model as the Innovation to Support Students’ Character Building - Ardiansyah, Suriadi; Komalasari, Kokom; Maryani, Enok; Wiyanarti, Erlina (Indonesian Values and Character Education Journal, 2024)
Advances in technology and information in the digital era, have an important role in the world of education. Including the use of media can support social studies learning in schools. Utilizing computers, laptops, gadgets, and the like as student learning media. Learning by utilizing technological media is needed in the era of the 21st century. On the contrary, technological sophistication negatively affects the character and morality of students. This study aims to design a social studies electronic book model based on local wisdom Nggusu Waru as student character building. The research design in this article uses Research and Development design at the development stage with a model developed by Borg & Gall. With several stages, namely research and information collection, this stage includes literature study activities, field observations, and Focus Group Discussion (FGD) to develop social science electronic book products, this research develops a social studies book based on local wisdom Nggusu Waru for student character building through Research and Development design. The results of the analysis in the discussion of the development of social studies e-books were declared suitable for use as learning media in schools based on the results of Focus Group Discussions with experts. Student responses also show a positive response to the existence of a social science e-book model based on local wisdom that can be useful in building student character.